IMPLEMENTASI AKUNTANSI PER TANGGUNGJAWABAN PADA PERUSAHAAN XYZ - Febrian Kresna Permana; Hani Sirine (Asian Journal of Innovation and Entrepreneurship, 2016)
This study aims to determine the implementation of responsibility accounting on trading company and to identify advantages and disadvantages of responsibility accounting in the company. Results of this study will illustrate the performance of the responsibility centers of company as a profit center, cost center, and the center of investment. In addition, this study will analyze the causes and effects of the performance of corporate responsibility centers. This study uses a trading company be located in Kupang as research objects. The data used is quantitative data in the form of financial statements 2010-2014 and qualitative data in the form of an interview to the organization committee of the company.